Structural stability of SrZrO3 perovskite and improvement in electronic and optical properties by Ca and Ba doping for optoelectronic applications: a DFT approach. Issue 24 (17th December 2019) - Gillani, S. S. A.; Ahmad, Riaz; Zeba, I.; Islah-u-din,; Rizwan, Muhammad; Rafique, Muhammad; Shakil, M.; Jabbar, Saqib; Siddique, M.
ABSTRACT: A detailed theoretical study, based on density functional theory (DFT) with GGA-PBE, of electronic, optical and structural properties of calcium (Ca) and barium (Ba)-doped SrZrO3, is presented. The doping influence on the electronic structure and consequently optical properties are analysed and explained with TDOS and PDOS. Structural parameters vary by partial replacement of strontium (Sr) atom with Ca and Ba in SrZrO3, separately, and PDOS modify themselves with the development of new states at symmetry points and as a result reduction in the electronic band gap is observed. We have also noticed that the indirect band gap of pure SrZrO3 is altered to the direct band gap after doping. The optical properties of the pure and doped SrZrO3 are interrelated with their electronic determinations. The considerable change in the band structure and optical properties by doping of Ca and Ba assert that the doped material is a more attractive contestant for optoelectronic device applications as compared to pure SrZrO3 .